2014
DOI: 10.1016/j.jaut.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Kv1.3 in psoriatic disease: PAP-1, a small molecule inhibitor of Kv1.3 is effective in the SCID mouse psoriasis – Xenograft model

Abstract: Kv1.3 channels regulate the activation/proliferation of effector memory T cells and thus play a critical role in the pathogenesis of autoimmune diseases. Using a combination of immunohistochemistry, confocal microscopy, flow cytometry and electrophysiology methods we observed a significant enrichment of activated Kv1.3+ memory T cells in psoriasis plaques and synovial fluid from patients with psoriasis/psoriatic arthritis (PsA) compared to non-lesional psoriatic skin, normal skin or peripheral blood lympho-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…However, compared to activated T‐cells and microglia in inflammatory lesions,18, 34 neuronal Kv1.3 staining is typically faint and often only observable with higher antibody concentrations and long incubation times 33. In agreement with these findings, we did not note any significant Kv1.3 staining on neurons, astrocytes, or surveillant microglia in normal mouse brain (data not shown) when using anti‐Kv1.3 antibody concentrations that stain activated lymphocytes in our hands 7, 35…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, compared to activated T‐cells and microglia in inflammatory lesions,18, 34 neuronal Kv1.3 staining is typically faint and often only observable with higher antibody concentrations and long incubation times 33. In agreement with these findings, we did not note any significant Kv1.3 staining on neurons, astrocytes, or surveillant microglia in normal mouse brain (data not shown) when using anti‐Kv1.3 antibody concentrations that stain activated lymphocytes in our hands 7, 35…”
Section: Resultssupporting
confidence: 87%
“…Interest in Kv1.3 afterward waned but revived following reports from our group that Kv1.3 is overexpressed in activated CCR7 − effector memory T‐cells (T EM ) and that Kv1.3 blockers therefore constitute immunomodulators rather than general immunosuppressants 3, 4, 5. Subsequent proof‐of‐concept animal studies demonstrated that the Kv1.3 blocking sea anemone Stichodactyla helianthus peptide ShK and its derivatives treat rat models of multiple sclerosis and rheumatoid arthritis,4, 5, 6 while our small molecule Kv1.3 blocker PAP‐1 prevents autoimmune diabetes4 in rats and treats psoriasis in a mouse xenograft model 7. As Kv1.3 blockers preferentially target T EM cells, Kv1.3 blockers do not impair the ability to clear acute infections or develop vaccine responses.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, the small molecules Psora-4 and PAP-1 [5-(4-phenoxybutoxy)psoralen]—both of which have low nanomolar potency—prevent antiglomerular basement membrane glomerulonephritis, autoimmune diabetes, and allergic contact dermatitis in rats (220, 221, 369). K V 1.3 blockers are also effective in models of psoriasis and alopecia areata (370371a), both diseases in which T EM cells are involved in the pathogenesis. In many of these studies, K V 1.3 blockers preferentially inhibited IL-2, IFN-γ, and IL-17 production by human or rat T EM cells but had little effect on TNF-α or on cytokines produced by naive and T CM cells (220, 221).…”
Section: Ion Channels As Drug Targets For Immunotherapymentioning
confidence: 99%
“…In previous studies, the overexpression of Kv1.3-channels was demonstrated in cells under such pathologic conditions, including cancer [78,79], ischemic heart disease [80], and autoimmune disorders [81,82]. In autoimmune disorders, such as rheumatoid arthritis [63,81], multiple sclerosis [83][84][85], type-I diabetes mellitus [63], and psoriasis [86,87], the inhibition of the Kv1.3-channel modulated the Ca 2? influx patterns in T lymphocytes, and thus actually exerted therapeutic efficacies for the diseases (Table 1).…”
Section: Targeting Lymphocyte Kv13 In ''Chronic Inflammatory Diseases''mentioning
confidence: 99%
“…Modified from Ref. [31] autoimmune disorders [63,81,[83][84][85][86][87][88][89][90], renal diseases [61,91,92], and respiratory disease [93,96,123] (Table 1). However, the therapeutic efficacies of these compounds were for the most part observed only in experimental animal models.…”
Section: Calcium Channel Blockers Statins and Nsaids As Potent Kv1mentioning
confidence: 99%